The art of the steal - Argott, Don (Orland Park, IL : MPI Home Video, 2010)
Follows the events after the death of art collector Albert C. Barnes as a power struggle develops over control of his $25 billion collection of paintings by Renoir, Cezanne, Matisse, Van Gogh, and other masters, housed in Lower Merion, Penn.
MPAA rating: Not rated.
DVD.
In English with optional English or Spanish subtitles.
Keywords: Barnes, Albert C. -- 1872-1951.; Barnes Foundation -- Management; Art -- Private collections -- Pennsylvania -- Merion; Decedents' estates; Art museums -- Pennsylvania; Art museums and community; Nonfiction films; Feature films; Documentary films